Anxiety in Pregnant Women during Covid-19 Pandemic in Banyuurip Frans Sudjiati Private Midwife Center, Surabaya - Veronica Silalahi (Jurnal Keperawatan, 2021)
Introduction: The psychological changes felt by pregnant women, one of which is anxiety, especially during the current Covid-19 pandemic. Prenatal anxiety, whether during a pandemic or not, is a risk factor for the emergence of pregnancy health complications for the mother and the fetus. Objective: This study aims to describe the level of anxiety of pregnant women during the pandemic at Banyuurip Frans Sudjiati Midwives Private Midwife Center, Surabaya. Method: The design of this study is descriptive with the research population of pregnant women who check their pregnancies at Banyuurip Frans Sudjiati Private Midwife Center. The sampling technique used simple random sampling with a sample size of 35 respondents. The instrument of this study used the PRAQ-r2 (Pregnancy-Related Anxiety Questionnaire-Revised 2) measurement tool. Result: The results showed that 48.9% of pregnant women had moderate anxiety, 42.9% mild anxiety, 5.7% not anxious, and 2.9% severe anxiety. Conclusion: The coronavirus pandemic indeed increases anxiety in pregnant women which will need to be addressed to avoid negative impacts on the mother and unborn child in Banyuurip Frans Sudjiati Private Midwife Center, Surabaya